MANISFESTASI KONSEP TA'ÂWUN DALAM ZAAKWAARNEMINGPERSPEKTIF HUKUM PERIKATAN - Galuh Widitya Qomaro (Et-Tijarie, 2018)
ABSTRAKHumans as social beings always need help from others. There needs to be a harmonious relationship between human beings for the peaceful life. One way to maintain this condition is to have a sense of empathy and sympathy. A form of good attitude of empathy and sympathy in society which is categorized as legal action is zaakwaarneming. In the Civil Code (KUHPerdata) zaakwaarneming is referred to as a voluntary representative where someone represents someone's interests or carries out the affairs of another person, voluntarily to do the help until the end or until the person those who are managed by their interests are able to do their own business. This paper attempts to discuss zaakwarneming in terms of legal norms, social norms and Islamic norms. ABSTRAKManusia sebagai makhluk sosial selalu membutuhkan adanya bantuan dari orang lain. Diperlukan adanya hubungan harmonis antara sesama manusia agar kehidupan yang tentram dan damai dapat terwujud. Salah satu cara untuk menjaga kondisi tersebut adalah dengan memiliki rasa empati dan simpati.Wujud sikap empati dan simpati yang baik dalam masyarakat yang dikategorikan sebagai tindakan hukum salah satunya adalahzaakwaarneming.Di dalam Kitab Undang-undang Hukum Perdata (KUHPerdata)zaakwaarnemingdisebut sebagai perwakilan sukarela dimana seseorang mewakili kepentingan seseorang ataumelakukan pengurusan suatu urusan orang lain, secara sukarela baik dengan sepengetahuan maupun tanpa sepengetahuan yang diwakili, terikat untuk melakukan perbuatan itu sampai selesai atausampai orang yang diurus kepentingannya mampu untuk melakukanurusannya sendiri.Paper ini berusaha membahas mengenai zaakwarneming dalam pandangan norma hukum, norma sosial dan norma agama Islam. Keyword:Zaakwaarneming, Ta'âwun, Islam.